Competency of Islamic Economic Jurisprudence as the Foundation of Human Resources in Islamic Economics - Romadhon, Romadhon; Saputra, Refki (RAFAHIYA Jurnal Ekonomi dan Syariah, 2025)
Abstracts in English, with 150-250 words and given a minimum of 3 keywords and a maximum of 5. Abstracts contain important things related to the article, including objectives, research methods, population and sample/object of research, research instruments, and research results. Islamic Economics has experienced significant development and is expected to offer solutions to various economic challenges amid the dominance of the capitalist system. A solid and comprehensive understanding of Islamic Economic Jurisprudence (Fiqh al-Muamalat) is essential as the philosophical foundation and practical basis for its implementation. Capacity building in Islamic Economic Jurisprudence is a critical and urgent necessity to ensure that economic activities proceed in accordance with Shariah principles and regulations. Therefore, constructing competencies in Islamic Economic Jurisprudence is an inevitable demand to produce human resources capable of providing guidance and jurisprudential perspectives across various Islamic economic activities, including production, distribution, transactions, banking, and others. The competencies required in Islamic Economic Jurisprudence include mastery of Fiqh al-Muamalat literature, proficiency in analyzing Shariah texts, skills in formulating jurisprudential perspectives, expertise in legal rulings, command of analogical reasoning (qiyas), ability to identify jurisprudential principles, understanding of Maqashid al-Shariah, and foundational knowledge of economics and economic regulations.